Studying the usability on various types of programming mobile applications / Wan Anisha Wan Mohammad, Azlina Mohd Mydin and Syarifah Adilah Mohamed Yusoff - Wan Mohammad, Wan Anisha; Mohd Mydin, Azlina; Mohamed Yusoff, Mohamed (UiTM Press, 2020)
In this new era of technology, smartphone has been widely used. To cope with the vast usage of smartphone, many kinds of mobile application or mobile apps has been developed. Besides social mobile apps, educational mobile apps are also one of the most popular application among users. For those who learn programming, many programming mobile apps are available on iOS and Android platform. Thus, this paper will study on the usability on various types of programming mobile apps such as CaptainCStudy for iOS, C++ Programming for Android and Learn C++ for both iOS and Android. A survey has been done to find the usability of the apps based on the interface and layout, content and activity provided. Result shows that each of the apps has its own style of delivering the information. Besides being able to type programming sytax, the programming mobile apps also provide various information for the knowledge of the students and even exercises which can help students understand programming easily.